2013
DOI: 10.1039/c3cc47549b
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-ion batteries using ion exchange membranes as electrolytes and separators

Abstract: New sodium-ion batteries using ion exchange membranes swollen with nonaqueous solvents as both electrolytes and separators have been first demonstrated, which show not only higher reversible specific capacity, but also better cycling stability compared with the conventional sodium-ion batteries using a liquid electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…Interestingly, the voltage profiles in the battery electrodes decline marginally as shown by the next charge/discharge process. This kind of small voltage results from faster chemical kinetics that corresponds to the improved coulombic efficiency [4,36,37]. The overall performance of the cell was found to be good considering the very little capacity loss per cycle.…”
Section: The Galvanostatic Charging/dischargingmentioning
confidence: 93%
See 3 more Smart Citations
“…Interestingly, the voltage profiles in the battery electrodes decline marginally as shown by the next charge/discharge process. This kind of small voltage results from faster chemical kinetics that corresponds to the improved coulombic efficiency [4,36,37]. The overall performance of the cell was found to be good considering the very little capacity loss per cycle.…”
Section: The Galvanostatic Charging/dischargingmentioning
confidence: 93%
“…It is also concluded that the testing membrane with liquid electrolyte 1M NaClO 4 -EC: DEC (1:1 by weight) changes to yellow color after prolonged cycling. Electrochemical decomposition of the liquid electrolyte to sodium alkoxide and alkyl carbonate which is yellow in color can be influential in the gradual increase of potential difference in charge/discharge cycling leading to fade in capacity [4]. The gradual decrease of Columbic efficiency with cycles has many possible origins and often, parasitic reactions as mentioned above or overhung in anode are cited as the reasons.…”
Section: The Galvanostatic Charging/dischargingmentioning
confidence: 98%
See 2 more Smart Citations
“…

In contrast to the large number of suitable electrode materials, thorough comprehension of the electrolyte remains lacking. [8][9][10][11] Although ceramic-based solid-state electrolyte have attracted much attention due to their high ionic conductivity at room temperature, harsh synthetic conditions (for instance, more than 1000 °C and 24 h) and poor contact capability with the electrodes are the main obstacles. Therefore, the discovery of an effective electrolyte remains a major challenge, which hinders the further application of SIBs.

…”
mentioning
confidence: 99%